Electrochemical Characterization of Gold Electrodes Modified With 1-Hexadecanethiol in Different Ratios of Water/Ethanol - Menolasina, Sabino (Ciencia, 1970)
Gold disc electrodes were fabricated using gold wires of 1mm and 60 Âµm diameter. Scanning electron microscopy (SEM) was used to determine the surface real shape, and to obtaine information about the quality of the seal at the electrode material-insulator material interface. These electrodes were modified with 1-hexadecanethiol in different ratios of water/ethanol solutions. The adsorption of 1-hexadecanethiol on gold electrodes from different ratios of water/ethanol was studied by differential capacitance measurements and heterogeneous electron transfer measurements. These studies showed that low defect density monolayers of 1-hexadecanethiol can be deposited on gold electrodes in a short time of exposure of the electrode in a solution prepared of this thiol in water/ethanol (1:1).